Fecal β-glucuronidase activity differs between hematopoietic cell and kidney transplantation and a possible mechanism for disparate dose requirements. (31st December 2022) - Khan, Mohammad Haneef; Onyeaghala, Guillaume C.; Rashidi, Armin; Holtan, Shernan G.; Khoruts, Alexander; Israni, Ajay; Jacobson, Pamala A.; Staley, Christopher
ABSTRACT: The intestinal microbiota produces β-glucuronidase that plays an essential role in the metabolism of the immunosuppressant mycophenolate mofetil (MMF). This drug is commonly used in organ and hematopoietic cell transplantation (HCT), with variations in dosing across transplant types. We hypothesized that β-glucuronidase activity differs between transplant types, which may account for differences in dosing requirements. We evaluated fecal β-glucuronidase activity in patients receiving MMF post-allogeneic HCT and post-kidney transplant. Kidney transplant patients had significantly greater β-glucuronidase activity (8.48 ± 6.21 nmol/hr/g) than HCT patients (3.50 ± 3.29 nmol/hr/g; P = .001). Microbially mediated β-glucuronidase activity may be a critical determinant in the amount of mycophenolate entering the systemic circulation and an important factor to consider for precision dosing of MMF.